Máquinas moleculares sintéticas: tetraalquil[2]rotaxanos como modelo no estudo de interações intramoleculares e intermoleculares - Rodrigues, Leticia Valvassori (2017)
This work presents the study of intramolecular and intermolecular interactions in tetraalkylsuccinamide[2]rotaxanes. These compounds have two submolecular components interlocked being obtained through a supramolecular self-arrangement. The submolecular components are: a thread, equipped with succinamide stations (R1R2NC(O)CH2CH2C(O)NR1R2) and different stoppers (R1R2: Pr, Bu, i-Bu and CH2Cy/CH2Ph); and a macrocyclic component derived from tetralactam. The molecular environment study of these compounds was analyzed in the solid state by data obtained by X-ray diffraction and in the liquid state by variable temperatures NMR experiments. The solid state study was carried out through several tools including maps of molecular electrostatic potential, calculations of quantum mechanics and Quantum Theory of Atoms in Molecules. In the liquid state the [2]rotaxanes behave as Molecular Machines because of the ability of the macrocyclic component to rotate around the thread. For the pirouetting movement the intramolecular interactions is broking. The data of the intramolecular interactions in solid state were correlated with the kinetic data for the pirouetting process of the macrocycle around the thread. The partitioning of the intramolecular interactions energy through the analysis of the Quantum Theory of Atoms in Molecules allied to the DFT calculations made it possible to identify the energy contribution of each fragment of the thread in the intramolecular interactions and in the Molecular Machine movements. The analysis of the molecular environment has shown that the variation of the stoppers in the thread affects the rates for the pirouetting movement since it modifies the intramolecular interactions between thread and macrocycle. The electrostatic potential maps demonstrated the electrostatic complementarity between the two interlocked submolecular components. For the study of the supramolecular environment, the supramolecular cluster was determined through the appropriate methodology. All the dimers were analyzed by calculations of quantum mechanics and data of the Quantum Theory of Atoms in Molecules. The partitioning of the energies of the interactions (by the Quantum Theory of Atoms in Molecules together with the DFT calculations) made it possible to analyze which of the submolecular components influences more effectively the crystal packing of these compounds. Intermolecular interactions were hierarchized according to their energies and crystallization mechanisms were proposed. The proposed mechanism of crystallization for the study compounds shows the differences between the [2]rotaxanes with Z '> 1 (solvates and confomers). The structure of the individual macrocyclic component was used in this study to compare with [2]rotaxane evidencing the effect of the thread in the crystal packing and crystallization mechanism. In the proposed mechanism of crystallization all the consequence dimers were considered. As an alternative method the crystalline retrosynthesis was proposed for a study compound model based on the principle of the supramolecular cluster decomposition according to the energy required to "break" the crystal along one direction. The energies of intramolecular and intermolecular interactions were obtained using the ωB97X-D/cc-pVDZ method with BSSE to reduce the overlapping error of the base set.